PEMANFAATAN HASIL HUTAN TANPA DISERTAI SURAT KETERANGAN SAHNYA HASIL HUTAN KAYU (SKSHHK) DI WILAYAH KABUPATEN TANAH LAUT: Utilization Forest Products Without Accompanied Certificate Validity Of Timber Forest Products (SKSHHK) In The Tanah Laut Regency Area - Andra Geofany Riswan; Irene Mariane (Reformasi Hukum Trisakti, 2024)
Indonesia is a country where the majority of the population is workers in the agricultural and forestry sectors. But there are still many violations of his forestry. The problem How is the permit for the transportation of timber forest products after the enactment of Article 12 letter e and Article 83 UUCK? And How is the application of the transportation of timber forest products without being accompanied by a SKSHHK in Decision Number 9/Pid.Sus/2020/Pn.Pli?. Research methods are normative laws, descriptive properties, secondary data sources and analyzed qualitatively by drawing deductive conclusions. In conclusion, in terms of permits for the Transportation of Timber Forest Products that must be fulfilled after the enactment of the UUCK, namely the permits regulated in its implementing rules, namely Article 259 number (1) that should be fulfilled in the transportation of timber forest products by the accused ATMAWI aka AWI should be in accordance with Minister of Environment and Forestry Number 8 of 2021. It should also be noted that the SKSHHK itself can only be issued after the ATMAWI defendant is supposed to fulfill PNBP's obligation to serve forest product transportation documents.